Scale effect of amount of molten corium and outlet diameters on corium spreading. (December 2020) - Yokoyama, Ryo; Suzuki, Shunichi; Okamoto, Koji; Harada, Masaru
Abstract: The difference in the amount of molten corium and outlet diameter influences the corium spreading, which is essential to enhance the safety of nuclear power plants. To investigate this phenomenon, in this work, the influence of the scale relation between the amount of molten metal and the outlet diameter (L/D) on the corium spreading was investigated. Experiments involving the spreading of a molten corium simulant on a stainless-steel plate were performed under various nozzle sizes and sample amounts. The spreading behavior during the experiment was recorded via a video camera. Based on the obtained experimental data, a dimensionless analysis was performed to determine the dominant parameters responsible for the spreading phenomena, and spreading models were developed to infer the solidified area and thickness. The results indicated that the spreading mode may vary at approximately L/D = 6, owing to the change in the force balance represented by the Weber and Reynolds numbers. The developed spreading model considering both the length and thickness values can help understand and predict the spreading of the fuel debris in the first floor. Graphical abstract: Image 1 Highlights: Studied scale effect of molten corium amount and outlet size on corium spreading. Spreading models developed for both spreading length and thickness. Two types of spreading modes occur, depending on the L/D. Weber number, Reynolds number, and L/D influence solidified spreading area.